Land use planning: Legal Regime - González-Varas Ibáñez, Santiago (2022)
Despite the progress in the field of land use planning, it continues to be somewhat bureaucratic and sometimes far from social reality. The practice perspective shows that supralocal planning arises from the need to articulate business and local projects. Territory planning should not neglect this basic dimension attached to the reality of the “supralocal project”. You should also think about solving problems that arise in Municipalities and companies when they have a supralocal nature. In Spanish law there has been a progressive effectiveness of land use planning. A decisive step has been taken in recent years, betting on a model of strict regulatory binding (without prejudice to the nuances or levels or degrees of binding, full, basic, etc.) of the territorial planning instruments on urban plans. In this way, it is possible to grant practical virtuality to land use planning, opening an interesting way to advance in the practice of land use planning and overcome the limitations of urban planning and some of its traditional problems.